Antônio Conselheiro e as prédicas do Belo Monte: palavra e fé no sertão - Gomes, Paulo Bibiano da Silva (2019)
This dissertation aims to emphasize the Antônio Vicente Mendes Maciel’s speech (1830-1897), Antônio Conselheiro, through the critical reading of his sermons, as stated in the work Antônio Conselheiro and Canudos (1997), published by José Carlos de Ataliba Nogueira (1901-1983). Antônio Conselheiro was the leader of a large group of northeastern people, who lived in Sertão, in the largest social movement in the history of Brazil: the community of Belo Monte, or Canudos (1893-1897). By founding his camp he dared to reinvent the backcountry, by adopting alternative ways of governing, producing and distributing wealth, integrating the social and spiritual dimension into community life, in an attempt to minimize the socioeconomic differences resulting from more than three centuries of colonization and aggravated by the climatic adversities typical of the Bahia’s northeastern and the northeast of Brazil. In this work, Antonio Conselheiro's manuscripts testify before history about his religious, philosophical and political thought. Written with remarkable discursive ability, his writing constitutes a counterpoint to the various discourses propagated by the hegemonic historical-literary representations, which punctuated him as a religious fanatic, madman, rude Gnostic, retrograde, great man inside out, holder of a barbaric oratory, astonishing, strange and dreadful, among other pejorative adjectives that were commonly attributed to him. This research is bibliographic and qualitative, and the arguments developed are supported by theoretical sources of authors such as Lippman (2010), Chartier (1990), Moniz (1997), Pesavento (2004), White (1995), Sevcenko (2003), Santos (2007), Costa Lima (2006), Arruda (2006), Calasans (1987; 1997; 2000), Hutcheon (1991), among others that will appear throughout the text.